Evaluation of Pulmonary Infiltrate in Febrile Neutropenic Patients of Hematologic Malignancies - Das, Chandan K; Gogia, Ajay; Kumar, Lalit; Sharma, Atul; Thulkar, Sanjay; Xess, Immaculata; Madan, Karan (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Pulmonary infection is the major risk during neutropenia induced by chemotherapy as well as stem cell transplantation. In spite of potent new-generation antifungal and broad-spectrum antibiotics, one-third of patients usually die from infectious complications. Early diagnosis and prompt administration of appropriate therapy improve the survival. Materials and Methods: We prospectively carried out the study to identify the infectious etiology of pulmonary infiltrates in febrile neutropenia patients by imaging and bronchoscopy. Bacterial culture, fungal culture, galactomannan and molecular diagnosis for pneumocystis, and other infectious agent were carried out in the bronchoalveolar lavage (BAL) fluid and blood. Results: A total of 27 patients were evaluated. Half of the patients belonged to acute leukemia (46%). We had a diagnostic yield of 65% with the most common isolates being Gram-negative bacteria and Aspergillus species. Conclusion: Gram-negative organisms were the predominant infectious agents of pulmonary infection. Our finding emphasizes the importance of BAL in evaluating pulmonary infiltrates in neutropenic patients with hematological malignancies.
Keywords: Hematological malignancies; infection; pulmonary infiltrate